Screening for deafness-associated mitochondrial 12S rRNA mutations by using a multiplex allele-specific PCR method. Issue 5 (28th May 2020) - Ding, Yu; Lang, Jianyong; Zhang, Junkun; Xu, Jianfeng; Lin, Xiaojiang; Lou, Xiangyu; Zheng, Hui; Huai, Lei
Abstract: Mitochondrial 12S rRNA A1555G and C1494T mutations are the major contributors to hearing loss. As patients with these mutations are sensitive to aminoglycosides, mutational screening for 12S rRNA is therefore recommended before the use of aminoglycosides. Most recently, we developed a novel multiplex allele-specific PCR (MAS-PCR) that can be used for detecting A1555G and C1494T mutations. In the present study, we employed this MAS-PCR to screen the 12S rRNA mutations in 500 deaf patients and 300 controls from 5 community hospitals. After PCR and electrophoresis, two patients with A1555G and one patient with C1494T were identified, this was consistent with Sanger sequence results. We further traced the origin of three Chinese pedigrees. Clinical evaluation revealed variable phenotypes of hearing loss including severity, age at onset and audiometric configuration in these patients. Sequence analysis of the mitochondrial genomes from matrilineal relatives suggested the presence of three evolutionarily conserved mutations: tRNA Cys T5802C, tRNA Lys A8343G and tRNA Thr G15930A, which may result the failure in tRNAs metabolism and lead to mitochondrial dysfunction that was responsible for deafness. However, the lack of any functional variants in GJB2, GJB3, GJB6 and TRMU suggested that nuclear genes may not play active roles in deafness expression. Hence, aminoglycosides and mitochondrial genetic background may contribute to the clinical expression of A1555G/C1494T-induced deafness. Our data indicated that the MAS-PCR was a fast, convenience method for screening the 12S rRNA mutations, which was useful for early detection and prevention of mitochondrial deafness.